2010
DOI: 10.1103/physreva.82.043415
|View full text |Cite
|
Sign up to set email alerts
|

Connecting field ionization to photoionization via 17- and 36-GHz microwave fields

Abstract: Here we present experimental results connecting field ionization to photoionization in Li Rydberg atoms obtained with 17-and 36-GHz microwave fields. At a low principal quantum number n, where the microwave frequency ω is much lower than the classical, or Kepler frequency, ω K = 1/n 3 , microwave ionization occurs by field ionization, at E = 1/9n 4. When the microwave frequency exceeds the Kepler frequency, ω > 1/n 3 , the field required for ionization is independent of n and given by E = 2.4ω 5/3 , in agreeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
14
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 33 publications
6
14
0
Order By: Relevance
“…which is in excellent agreement with the experimental observations of Shuman et al [10] and Gurian et al [12]. In Fig.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…which is in excellent agreement with the experimental observations of Shuman et al [10] and Gurian et al [12]. In Fig.…”
supporting
confidence: 93%
“…Collectively, these observations suggest that quasi stable Floquet states are formed in both cases, as suggested by Gurian et al and Tong et al [12,14]. In the He case, there are bound levels of He separated by frequencies close to the IR frequency, so it is easy to imagine a quasi stable wave packet based on these coupled states.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…Although one might expect the classical model to work better for higher n states, where Ω > 1, it predicts that at a fixed frequency the microwave field required for ionization decreases with n [6]. However, experiments have shown that for Ω > 1 the ionization field only depends on the microwave frequency until the initial binding energy is within a few microwave photons of the ionization limit [7,8]. When the initial Rydberg state is within one or two microwave photons of the ionization limit, we would expect perturbation theory to give an accurate prediction of the ionization rate.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments such as the ones in Refs. [9,10] have suggested that the ratio of the laser frequency ω to the classical orbital frequency ω K of the bound electron, i.e., ω/ω K , could be just as relevant in deducing the dominant physical mechanisms as the laser frequency ω itself. This ratio is termed the scaled frequency and is given by = ωn 3 for atoms.…”
Section: Introductionmentioning
confidence: 99%